Interrogating the Prevention Approach of the Housing (Wales) Act 2014 for People with Mental Health Needs Who Are Homeless. Issue 1 (15th October 2019) - Rogers, Michaela; Ahmed, Anya; Madoc-Jones, Iolo; Gibbons, Andrea; Jones, Katy; Wilding, Mark
Abstract : Rates of homelessness and poor mental health present significant challenges across the globe. In this article, we explore how these intersecting issues have been addressed in Wales through Part 2 of the Housing (Wales) Act 2014 through a paradigm shift towards a prevention model. This article reports findings from a study (conducted between 2016 and 2018) which evaluated the processes and impacts of the Act against the backdrop of welfare reform and systemic changes taking place in Wales and the UK. Using new evidence, we offer a critical examination of how homelessness prevention policy operates in practice and how social values and power affect policy implementation. We offer new evidence of the translation of policy into practice through the experiences of two stakeholder groups: people with mental health needs and service providers. In doing so, we offer a critique of how policy and practice could be modified to improve outcomes for homeless people with implications for prevention policy in Wales and in other contexts and different welfare regimes.